ICASSP 2019 - 2019 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2019
DOI: 10.1109/icassp.2019.8683453
|View full text |Cite
|
Sign up to set email alerts
|

Speech Recognition with No Speech or with Noisy Speech

Abstract: In this paper we demonstrate continuous noisy speech recognition using connectionist temporal classification (CTC) model on limited Chinese vocabulary using electroencephalography (EEG) features with no speech signal as input and we further demonstrate single CTC model based continuous noisy speech recognition on limited joint English and Chinese vocabulary using EEG features with no speech signal as input.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 30 publications
1
60
0
Order By: Relevance
“…In [1] we have demonstrated that EEG sensors T7 and T8 features contributed most towards ASR performance. Table VI shows the CTC model test time results when we trained the model using EEG features from only T7 and T8 sensors on the most noisy data set B.…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…In [1] we have demonstrated that EEG sensors T7 and T8 features contributed most towards ASR performance. Table VI shows the CTC model test time results when we trained the model using EEG features from only T7 and T8 sensors on the most noisy data set B.…”
Section: Resultsmentioning
confidence: 86%
“…EEGlab's [18] Independent component analysis (ICA) toolbox was used to remove other biological signal artifacts like electrocardiography (ECG), electromyography (EMG), electrooculography (EOG) etc from the EEG signals. We extracted five statistical features for EEG, namely root mean square, zero crossing rate,moving window average,kurtosis and power spectral entropy [1]. So in total we extracted 31(channels) X 5 or 155 features for EEG signals.The EEG features were extracted at a sampling frequency of 100Hz for each EEG channel.…”
Section: Eeg and Speech Feature Extraction Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…In [23] authors demonstrate that electroencephalography can be used for better performance of ASR system in the presence of noise. They used distillation training and showed that this training can improve the accuracy of an ASR system with EEG features in background noise.…”
Section: Review Of Literaturementioning
confidence: 99%